2010
DOI: 10.3171/2010.2.jns09376
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long-term shunt-dependent hydrocephalus after aneurysmal subarachnoid hemorrhage

Abstract: These data suggest that permanent CSF diversion after aneurysmal SAH may be independently predicted by hyperglycemia at admission, findings on the admission CT scan (Fisher Grade 4, fourth ventricle intraventricular hemorrhage, and bicaudate index ≥ 0.20), and development of nosocomial meningitis. Future research is needed to assess if tight glycemic control, reduction of fourth ventricle clot burden, and prevention of nosocomial meningitis may reduce the need for permanent CSF diversion after aneurysmal SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
84
5
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 26 publications
6
84
5
2
Order By: Relevance
“…5 A prior inves tigation found no association between shuntdependent hydrocephalus and admission neurological status in pa tients with SAH, in agreement with previous ICH cohort data as well as results from our univariate analysis. 23 Interestingly, development of shuntdependent hy drocephalus was more likely in those patients with a tha lamic hemorrhage, but independent of other hemorrhage locations or IVH volume, despite the fact that IVH is known to predict worse outcomes in patients with ICH in a volumedependent manner. 18,25 Given the anatomical relationship of thalamic hemorrhages to the third ven tricle and the foramen of Monro, it is intuitive that he matoma formation in this location more easily results in obstruction of CSF flow independent of IVH volume than in hemorrhages occurring in other locations.…”
Section: Discussionmentioning
confidence: 99%
“…5 A prior inves tigation found no association between shuntdependent hydrocephalus and admission neurological status in pa tients with SAH, in agreement with previous ICH cohort data as well as results from our univariate analysis. 23 Interestingly, development of shuntdependent hy drocephalus was more likely in those patients with a tha lamic hemorrhage, but independent of other hemorrhage locations or IVH volume, despite the fact that IVH is known to predict worse outcomes in patients with ICH in a volumedependent manner. 18,25 Given the anatomical relationship of thalamic hemorrhages to the third ven tricle and the foramen of Monro, it is intuitive that he matoma formation in this location more easily results in obstruction of CSF flow independent of IVH volume than in hemorrhages occurring in other locations.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7]11,12,16,18,23 On the basis of the evidence of an association between the severity of SAH and the prevalence of subsequent sNPH, many neurosurgeons have believed that several surgical manipulations for facilitating CSF dynamics, such as hematoma evacuation, widening the opening of the cisterns, and fenestration of the lamina terminalis, might help to reduce the subsequent occurrence of sNPH after the surgical treatment of SAH. However, the authors of a recent meta-analysis of 11 nonrandomized studies in which data from 1973 patients were pooled concluded that there was no significant difference in the prevalence of sNPH between the 975 patients who had undergone fenestration of the lamina terminalis and the 998 who had not (p = 0.09).…”
Section: 24mentioning
confidence: 99%
“…[3][4][5][6]11,16 Previous studies have shown that severe symptoms at SAH onset and a large amount of subarachnoid blood seen on admission CT images are associated with the development of sNPH. [3][4][5][6][7][8][9][10][11]12,16,18,23 A posterior circulation location of the ruptured aneurysm and endovascular coil embolization have been reported to be significantly associated with sNPH. 1,[4][5][6][7]12,15,16,22 However, this relationship is controversial, because SAH caused by a posterior circulation aneurysm frequently occurs with severe initial symptoms and acute hydrocephalus, compared to SAH caused by a ruptured anterior circulation aneurysm, which is known to occur with mild symptoms and/or no acute hydrocephalus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, recognition of predictive variables and identifying patients at risk for shunt-dependent hydrocephalus (SDHCP) could lead to optimized management with avoidance of increased neurological morbidity, impaired functional outcome and quality of life, and extended hospital stays associated with chronic hydrocephalus. 3,9,14,15 The few published series on shunting after aSAH had short follow-up times, 2,4,[16][17][18] small samples, 2,3,5,6,[15][16][17][18][19][20] or used administrative databases, 12,[21][22][23] where there was an inherent problem of selection bias and uncontrollable factors that could influence the reported rate of shunt requirement. Case series are especially vulnerable to selection bias; studies that report on a series drawn from their patients from a particular population (eg, a hospital or clinic) may not appropriately represent the proportions in the wider population.…”
mentioning
confidence: 99%